A LINGUOCULTURAL ANALYSIS OF SYMBOLS AND METAPHORS IN THE WORK “FAHRENHEIT 451 DEGREES” (TAMADDUN NURI JURNALI, 2024)
This article analyzes Ray Bradbury’s “Fahrenheit 451” from a linguocultural perspective. It investigates how cultural symbols and metaphors are interpreted through language and culture in the novel. The study uses a linguocultural approach to provide deeper insights into the connections between literature, culture, and society.